2019
DOI: 10.1093/rheumatology/kez519
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation and heritability of ankylosing spondylitis – a Swedish nested case–control study

Abstract: Objectives AS is known to be a highly heritable disease, but previous studies on the magnitude of the familial aggregation and heritability of AS have been small and inconclusive, with familial relative risks ranging from 17 to 94. We aimed to improve estimates of these factors by studying families of all subjects diagnosed with AS in Sweden over a period of 16 years and to investigate if familial risks vary by sex or type of relative. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
2
19
2
1
Order By: Relevance
“…However, similar ratios were obtained in population-based studies in Iceland with a first-degree RRR ranging from 75 to 94 (Thjodleifsson et al, 2007;Geirsson et al, 2010). In contrast, two register-based case-control studies of AS patients in Sweden reported a substantially lower RRR with a sibling risk between 15 and 20 (Sundquist et al, 2008;Morin et al, 2019).…”
Section: Do As Cluster In Families?supporting
confidence: 71%
“…However, similar ratios were obtained in population-based studies in Iceland with a first-degree RRR ranging from 75 to 94 (Thjodleifsson et al, 2007;Geirsson et al, 2010). In contrast, two register-based case-control studies of AS patients in Sweden reported a substantially lower RRR with a sibling risk between 15 and 20 (Sundquist et al, 2008;Morin et al, 2019).…”
Section: Do As Cluster In Families?supporting
confidence: 71%
“…A distinctive feature of SpA is the high familial aggregation. We found a 20-fold increased risk of ankylosing spondylitis (AS) in first-degree relatives of AS patients (17), and even higher estimates have been reported (18)(19)(20). In psoriatic arthritis (PsA), 30-55 times higher risks are reported in first-degree relatives (21)(22)(23)(24).…”
mentioning
confidence: 83%
“…16 In a study of all patients diagnosed with r-axSpA in Sweden during a 16-year period, the overall familial odds ratio (OR) for r-axSpA was 19.4 (95% CI, 18.1 to 20.8), and patients with more than 1 family member with r-axSpA had a higher risk for development of the disease (OR, 60.8; 95% CI, 51.3 to 90.1) compared with patients with no known family history. 17 Several genetic risk factors have been associated with the development of axSpA. Among these, the presence of the genetic marker HLA-B27 is consistently and strongly associated with development of axSpA.…”
Section: The Starting Point: Genetic Predis-position To Axspamentioning
confidence: 99%